THE INFRASTRUCTURAL VIOLENCE OF THE USAID DATA CAPTURE - Madianou, Mirca (AoIR Selected Papers of Internet Research, 2026)
This paper traces the consequences of the decimation of the US Agency for International Development (USAID) for a refugee camp along the border between Thailand and Myanmar. Events in Washington DC in January 2025, had devastating effects in Mae La camp as medical care and other essential services were withdrawn overnight. A less discussed dimension of the crisis concerns the potential harms resulting from the capture of refugee sensitive data. The paper analyses these events as exemplars of ‘infrastructuring’ and ‘infrastructural violence’. Digital technologies and AI increasingly underpin humanitarian operations to the extent that they provide the infrastructure through which essential aid is delivered. A typical example is biometrics which is commonly used for the delivery of vital services in Mae La. As infrastructures transcend institutional boundaries and humanitarian systems become interoperable with those of private companies and nation-states, the opportunities for function creep increase. The shareability of data and the permanence of records mean that data collected for one reason may be used for entirely different purposes and by different actors than the humanitarian organisations. The infrastructuring of aid amplifies the risks to individuals and multiplies the opportunities for structural violence.